Effect of Music Therapy on Alzheimer’s Disease: How Music Combats Alzheimer’s Disease? - Mai, Gracelyn; Fan, Jeffery; Mai, Brandon; Fan, Xiujun (International Journal of Innovative Research in Medical Science, 2023)
Alzheimer’s disease, the most prevalent form of dementia, is a fatal neurodegenerative disorder. The risk factors of Alzheimer’s disease include age, genetics, lifestyle, and other external stressors. The Coronavirus disease 2019 (COVID-19) pandemic has brought along many changes and has exacerbated symptoms within persons with Alzheimer’s disease such as depression, anxiety, and agitation, with this also accelerating cognitive decline and mental health of patients with Alzheimer’s disease. COVID-19 has the capacity to increase risk of Alzheimer’s disease within healthy people, as it also has capacities to target the central nervous system. Though Alzheimer’s disease cases are continually rising dramatically, there is no cure. Current treatment options, such as drugs, are not easily accessible and have many limitations. As a result, non-pharmacological and easily accessible interventions, such as music therapy, have garnered interest. In this review, we summarized different music therapy techniques, outcomes of music therapy treatments, and the underlying mechanisms of music therapy. Though music therapy is a promising option for the treatment of Alzheimer’s disease, due to limited results concerning long term benefits, the combination of music therapy with other non-pharmacological interventions such as physical exercise should also be considered.